Knowledge of Reproductive Age Women About Oral Contraceptive Pills in Al-Qunfudah, Saudi Arabia [Corrigendum] - Al Basri SF; Al Abdali JA; Alzubaidi HM; Almarhabi AA; Alzubaidi MA; Al Qarni G; Alzubaidi NY; Aldabli A; AlMagaadi A; Alamri LA; AlQarni GS; AlAbdli AH; et al. (Dove Medical Press, 2022)
Al Basri SF, Al Abdali JA, Alzubaidi HM, et al. Open Access J Contracept. 2022;13:61–71. The authors have advised the affiliation list on page 61 is incorrect. The correct author list and affiliations are as follows. Samera F Al Basri,1,2 Jawaher A Al Abdali,3 Hala M Alzubaidi,3 Abeer A Almarhabi,3 Maryam A Alzubaidi,3 Gadi Al Qarni,3 Nada Y Alzubaidi,3 Aliyah Aldabli,3 Amna AlMagaadi,3 Laila A Alamri,3 Ghadeer S AlQarni,3 Areej H AlAbdli,3 Bashaier H AlGhamdi,3 Zahra A AlNashri3 1Obstetrics and Gynecology, King Abdulaziz University Hospital, King Abdulaziz University, Jeddah, Saudi Arabia; 2Faculty of Medicine, King Abdulaziz University, Jeddah, Saudi Arabia; 3Faculty of Medicine, Umm Al-Qura University, Al-Qunfudah, Saudi Arabia Read the original article